Association between Blood Donation and Malignant and Benign Tumour Risk: A Population-Based Study of 3.4 Million Participants in China. (8th July 2022) - Su, Shu; Ma, Ting; Sun, Yang; Guo, Lingxia; Su, Xiaodong; Wang, Wenhua; Xie, Xinxin; Wang, Liqin; Xing, Lili; Zhang, Leilei; He, Shiyi; Yang, Jiangcun; et al.
Abstract : This study aims to identify the relationship between blood donation and malignant and benign tumour hospitalization risk. The cohort study was constructed in Shaanxi, China, to include blood donors and match nonblood donors one-to-one by gender, age, and county of residence. The study compared the hospitalization records of two groups from 2012 to 2018. A log-binomial regression model was used to estimate the relative risk (RR) of tumour risk between donors and nonblood donors among different age groups. A total of 1, 625, 599 donors were recruited (including 968, 823 males) and compared with the matched nonblood donor group. Significantly lower risk of malignancy in males was found among donors (adjusted RR: 0.82, 95% CI: 0.75–0.92). Lower risks for specific types of tumours among donors were observed, including liver (0.42, [0.28–0.67]), lung (0.74, [0.59–0.87]), lymphoma (0.75, [0.62–0.85]), and oesophagus (0.55, [0.41–0.72]). However, the risk of brain cancer was higher among male donors (RR 1.19 [1.06–1.29]). Among female donors, lower risk of liver (0.57, [0.42–0.79]) and oesophagus malignancy (0.73, [0.62–0.88]) was observed. For benign tumours, male donors have a lower risk of benign skin tumour (0.79, [0.62–0.94]) and hemangioma and lymphangioma (0.75, [0.51–0.89]), while female donors have a lower risk in hemangioma and lymphangioma (0.65, [0.44–0.83]). We also found that the risk decreased with age among donors in the prevalence of tumours compared to that in nonblood donors (p < 0.05 ). Blood donation appears to be significantly associated with various tumour risks among both males and females. Overall, the risk of tumours decreased more substantially with age in blood donors compared with nonblood donors. Further research is warranted to investigate the impact of 'health donor effects' on these findings.